(untitled) (Journal Of Educational and Psychological Researches, 2017)
The aim of the present research is to construct a model to evaluate the software engineering subject in the third grade department of Computing, in colleges of education. Then, evaluating the software Engineering subject from the view point of staff members by applying the constructed model, and in order to achieve the second aim of the present research the researcher has to find answers to the following questions:- 1. What is the presence of the proposed evaluating model fields, which was prepared by the researcher for the third grade Soft Ware Engineering subject from the view point of staff members? 2. What is the presence of the items for the proposed evaluating model, which was prepared by the researcher for the third grade Soft Ware Engineering subject from the view point of staff members? To achieve the objectives of the research, the researcher used as a population of her research all the department of Computing staff members who taught Soft Ware Engineering subject for the current academic year 2014-2015 and the previous years, as well as the specialist who were presence at the meeting of the sect oral Committee in colleges of education for Iraqi Universities (Baghdad, Al-Mustansiriya, Diyala, Al-Iraqia, ThiQar ,Basrah, Hamdania, and Mosul), Totaling (58)staff members, The researcher has chosen intentionally four universities (Baghdad, al-Mustansiriya, Diyalaand al-Iraqia) to be the sample of her research. The researcher used a descriptive approach, and in order to prepare a list of items that are essential for the evaluating model as a first draft, the researcher has depended on previous studies in the field and on the opinions of (20) experts engaged in teaching distributed in colleges of education at Baghdad and al-Mustansiriya universities, through spreading an open ended questionnaire includes six questions, to propose what is suitable to be included in the evaluating model, The first list included the following six fields The list of items was distributed to a sample of (15), then the researcher gave them enough time to check each item and removing or adding what is suitable for the model to become in its final draft which included (125) items,The researcher followed up with (10) ten experts Delphi style throughout three rounds to reach the final form of the evaluating model, and there was a complete agreement among them ,The researcher applied the evaluating model in its final form among (40) staff members, and giving them enough time to answer. Answers were later analyzed statically by using a number of statistical methods and checked the results using (SPSS),It has been found that staff members agree on the achievement of all of the six evaluating model fields in software engineering subject and an achievement of (115) of the evaluating model items with percentage of (%92),The results showed an achievement of the subject aims and methods of teaching and students evaluation, It showed the marginalization of the applied side and focus on theory in all areas whether aims or content and even teaching methods and activities, evaluation, and the shortage of modernizing and developing the syllables section compatibility with showed few inclinations and interests of students.